2011
DOI: 10.1159/000319848
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained Somatic Symptoms during Major Depression: Prevalence and Clinical Impact in a National Sample of Italian Psychiatric Outpatients

Abstract: Background: The aim of this study was to explore the prevalence and impact of unexplained somatic symptoms during major depression. Sampling and Methods: A total of 560 consecutive outpatients with a major depressive episode according to the DSM-IV (text revision) were evaluated in 30 psychiatric facilities throughout Italy. ‘Unexplained’ somatic symptoms were evaluated using the 30-item Somatic Symptoms Checklist (SSCL-30). Somatic symptoms were considered explained if they were best accounted for as coming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 99 publications
2
16
0
Order By: Relevance
“…The present study is based on a post-hoc partial analysis of the database collected for a previous study, including 571 consecutive patients with a diagnosis of MDE, according to DSM-IV-TR, that were enrolled in a large cross-sectional, multicentre, observational study (COME TO ME) 9. The study involved 30 psychiatric outpatient facilities, distributed throughout Italy, investigating the prevalence of medically unexplained somatic symptoms in the course of MDE, which resulted in severe depressive symptomatology, high rates of misdiagnosis, and improper treatment and health resource utilization.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is based on a post-hoc partial analysis of the database collected for a previous study, including 571 consecutive patients with a diagnosis of MDE, according to DSM-IV-TR, that were enrolled in a large cross-sectional, multicentre, observational study (COME TO ME) 9. The study involved 30 psychiatric outpatient facilities, distributed throughout Italy, investigating the prevalence of medically unexplained somatic symptoms in the course of MDE, which resulted in severe depressive symptomatology, high rates of misdiagnosis, and improper treatment and health resource utilization.…”
Section: Methodsmentioning
confidence: 99%
“…The mean HCL-32 value in the study by Vancampfort et al [42], conducted in a group of 67 patients with bipolar disorder, was 15.80 ± 6.50. Perugi et al [43] found 15 or more hypomanic characteristics based on the HCL-32 in almost half of the studied group (n = 253, 45.2%).…”
Section: Discussionmentioning
confidence: 87%
“…The present study is based on a post-hoc partial analysis of the database collected for a previous study including 571 consecutive patients with a diagnosis of an major depressive episode (MDE), according to DSM-IV, who were enrolled in a large cross-sectional, multicenter, observational study (Come To Me) [31]. The study involved 30 psychiatric outpatient facilities, distributed throughout Italy, assessing the impact of medically unexplained somatic symptoms in course of an MDE and its relationship to the severity of depressive symptomatology, the risk for misdiagnosis and associated improper treatment and health resource overutilization.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the present study is to explore the factorial structure of HCL-32 in a large national sample of patients enrolled in a study exploring the presence of somatic symptoms during major depression [31] and to analyze the discriminative power of different factors in distinguishing non-bipolar from bipolar patients. Another goal of the study is to define some of the characteristics identified by the HCL-32, but not recognized by the patients (depending on the patient’s ability to recall hypomanic episodes and on the patient’s awareness that they represent part of the affective illness) or alternatively by the clinicians (depending on the clinician’s attitude in interviewing patients and in the interpretation of the hypomanic manifestations).…”
Section: Introductionmentioning
confidence: 99%